Implementasi Pendidikan Karakter Di Taman Pendidikan Al-Qur’an (Tpq) Terhadap Perkembangan Sosial Anak Usia Dini - Mukaromah, Luluk; Anas Rangga Buana Hanafi (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
This research is motivated by the current globalization that requires parents to pay attention to children's behavior and morals so that they can interact and socialize well. Given that character education is the main goal in early childhood education. So that character education is considered to be the responsibility of all aspects in early childhood education, not only formal and informal education but also non-formal education such as TPQ and the like. This research is case study research with a descriptive qualitative approach conducted at TPQ Al Mukhtar, Mlokorejo Village. The purpose of the research is to describe the implementation of the concept of character education in TPQ. The data collection techniques of this research are observation, interview, and documentation. The results show that the concept of character education at TPQ Al Mukhtar to achieve character education at a good level, in the sense that there is a balance between knowledge and charity of the Qur'an, also provides a model of habituation and scientific practice. So as to be able to form good early childhood behavior and morals. Furthermore, children are able to interact, socialize and socialize well. The implementation of early childhood character education is integrated with the material in the Qira'ati Thoriqoh Yanbu'a Method which contains the intention of wudhu', the intention of prayer (five times) itself being an imam and being a mum, daily prayers, hadiths related to daily life and short letters through habituation and repetition and memorization starting from the age of 3-8 years.